A five-year follow-up of a patient with fulminant myocarditis who underwent a stepwise and goal-oriented individualized comprehensive cardiac rehabilitation program - Sasanuma, Naoki (J Cardiol Cases, 2015)
A 39-year-old man developed fulminant myocarditis and was transferred on mechanical ventilation and a ventricular-assist device to our hospital. On Hospital Day 10, he was weaned from all medical engineering devices, and bedside rehabilitation was initiated. Although a multidisciplinary cardiac rehabilitation team had intervened since Hospital Day 3, he could not be encouraged to begin ambulation because of hypotension and tachycardia. Moreover, he complained of loss of self-confidence and anxiety regarding physical strength, and expansion of activities was difficult. Exercises reflecting his immediate desires and daily activities were used as activity goals, and we developed an individualized exercise program with stepwise increase in load to motivate him to perform rehabilitation. At the time of discharge, his cardiac function recovered to nearly normal levels; however, muscle strength and respiratory function had not recovered. While the intervention was continued at the cardiac rehabilitation outpatient unit, improvement was observed in physical health and mental health-related scale scores. The patient returned to work 4 months after onset of his myocarditis. Moreover, the cardiac rehabilitation team provided support to him for his long-term overseas assignment in the fifth year after myocarditis onset. Long-term comprehensive support by the cardiac rehabilitation team was feasible and useful. <Learning objective: Comprehensive intervention by a cardiac rehabilitation team from the acute phase may be helpful for motivating patients not only to participate in rehabilitation during hospitalization, but also to continue it on an outpatient basis after discharge. Moreover, continuous outpatient intervention can lead to recovery of physical/mental function in patients that is not achievable with only inpatient intervention, and support can be provided to patients for setting new life goals.>